Collaborative Governance dalam Kesiapsiagaan Bencana Gunung Sinabung di Kabupaten Karo Provinsi Sumatera Utara - Kurniaty, Evi Yunita; Effendy, Khasan; Kawuryan , Megandaru W.; Kurniawati, Layla (Universitas Medan Area, 2024)
This article aims to explain collaborative governance in Mount Sinabung disaster preparedness, focusing on the collaborative process. The problem centers on the Disaster Resilient Village which was formed by the Karo Regency BPBD, but during its establishment from 2019 to date, it has not implemented the Destana program in disaster preparedness. To answer this problem, the Collaborative Governance theory of Chris Ansell and Alison Gash is used. Data were collected through interviews and triangulation, as well as a literature review, and analyzed qualitatively. This study concludes the collaborative process of the Runggu of the Karo District Government on disaster management and the Runggu tradition in the village. Building trust by forming Destana and the Destana program that is included in the village budget. Commit to a joint agreement to prepare the documents for the Village Disaster Management Plan and Village Contingency Plan. Then the document is understood and implemented together according to their respective roles. This resulted in medium-term results in Gung Pinto Village receiving a Village Resilience rating in the Primary category. The findings from this study were that of the 14 villages formed, only 1 village could carry out the collaboration process well. With recommendations for the need for an empowerment process in collaborative governance in disaster preparedness at Mount Sinabung in Karo Regency, North Sumatra Province.